Forecasting Parameter Estimates: A Modeling Approach Using Exponential and Linear Regression - Ahmad, W. M. A. W.; Rohim, R. A. A.; Ismail, N. H. (Engineering, Technology & Applied Science Research, 2018)
This paper supplies a calculation method for the parameter estimates of an exponential equation through SAS algorithm. The aim of this paper is to investigate the efficiency of the gained parameter estimates through the forecasting performance. The proposed calculation method can provide a very useful technique to develop an exponential equation with better accuracy performance. This research paper illustrates a sample of the data obtained from the established study, which characterize the proliferative capacity of mesenchymal stem cells. This paper also provides the specific algorithm for the parameter estimates.